Pemberdayaan Masyarakat Melalui Sistem Pengelolaan Sampah Terintegrasi: Studi Kasus Desa Cidatar - Mirza Fathir; Angelica Mendi Amelia; Eghi Sutedjar; Hiban Kayis Abdilah; Rifki Firmansyah; Wildan Adiwinata; Silviani; Muhammad Fadil Sutiawan; Desti Yashfy Silmia; Andi Muhamad Ramdani; Mohammad Yasrul Ahlakul Alaby; Ahmad Pahruroji; Kaka Nugraha; Rd. Dzikry Rakhmati Nazar; Amarta Pratiwi Royani; Muhammad Rafly; Bagja Gumelar; Akmal Athallah Ramadhani; Rahma Nur Aliyah; Shah Riza Ramadhan (Institut Teknologi Garut, 2026)
The main problem in Cidatar Village is the suboptimal waste management and processing system. The community is still accustomed to disposing of waste directly without sorting it, which causes accumulation, environmental pollution, and potential health hazards. This condition shows the need to empower the community to increase awareness, skills, and active participation in sustainable waste management. This community service activity aims to build a structured waste management system by empowering residents to sort, process, and utilize waste into something useful. The method used is Participatory Action Research with a Work Breakdown Structure scheme that breaks down activities into preparation, implementation, and evaluation stages. The community service program was carried out through seminars on waste types, mapping waste bank locations, developing a management system in the form of operational standards, workflows, and operational schedules, designing waste banks and low-smoke combustion technology, and developing a waste bank recording application. The results of the activities showed an increase in residents' understanding, with an average post-test score of 80 percent. Thus, this activity not only provided education but also produced an integrated waste management system that is ready to be implemented by the community on a sustainable basis.